Experiment Investigation on Cooling Performance of Lithium-Ion Battery Thermal Management System Using Flat Heat Pipe - Anamtawach, Chokchai; Odngam, Soontorn; Sumpavakup, Chaiyut (2023 Research, Invention, and Innovation Congress: Innovative Electricals and Electronics (RI2C), 2023)
A thermal management system is important to remove heat generated during charge and discharge for lithium-ion batteries used in electric vehicles. It is crucial to identify the most effective, affordable, and lightweight solution, such as phase change materials and heat pipes, in order to provide minimal power consumption and effective heat transfer. Furthermore, heat pipe technology is an effective thermal management system for lithium-ion batteries, so it's critical to look into the feasibility of designing heat pipes as cooling systems. In this work, the thermal management system with flat heat pipes coupled with aluminum fins was designed to examine the thermal characteristics of the lithium nickel manganese cobalt oxide battery pack during various charge and discharge rate operations. The seven 20 Ah battery cells in series were used in this work to test the cooling performance of the proposed battery thermal management system relying on heat pipes. The cooling performance were compared with and without heat pipes coupled with aluminum fins. The experiments were performed at charge rates of 1 C and 2C and discharge rates of 1 C, 2C, 3C, and 4C at room temperature under natural convection. As a result, the maximum temperature of the battery cells and the maximum temperature difference between the battery cells were significantly reduced in all experiments.